Cancer in Systemic Sclerosis: Analysis of Antibodies Against Components of the Th/To Complex. Issue 2 (26th December 2020) - Mecoli, Christopher A.; Adler, Brittany L.; Yang, Qingyuan; Hummers, Laura K.; Rosen, Antony; Casciola‐Rosen, Livia; Shah, Ami A.
Abstract : Objective: The aim of this study is to describe 4 of the most common autoantibodies against components of the Th/To complex: human POP1 (hPOP1), RPP25, RPP30, and RPP40. We report their prevalence and clinical characteristics in a systemic sclerosis (SSc) population, and determine whether these specificities are associated with cancer. Methods: A case–control study was performed using data from the Johns Hopkins Scleroderma Center Cohort. A total of 804 adult patients with SSc were included; 401 SSc patients with no history of cancer after at least 5 years of disease were compared to 403 SSc patients who ever had a history of cancer. Antibodies against hPOP1, RPP25, RPP30, and RPP40 were assayed by immunoprecipitation of 35 S‐methionine–labeled proteins generated by in vitro transcription/translation. Demographic and clinical characteristics were compared between groups. Results: Of 804 patients, 67 (8.3%) had antibodies against any component of the Th/To complex. Patients with antibodies to any component were significantly more likely to have limited cutaneous disease, less likely to have tendon friction rubs, and more likely to have findings consistent with interstitial lung disease or pulmonary hypertension. Patients with antibodies against hPOP1, RPP25, RPP30, and/or RPP40 were significantly less likely to develop cancer within 2 years of SSc onset (0% versus 11% of antibody‐negative patients; P = 0.009). Conclusion: SSc patients who produce autoantibodies to components of the Th/To complex have a clinical phenotype characterized by limited cutaneous disease and pulmonary involvement. Our findings show that the presence of any Th/To autoantibody may have a protective effect against contemporaneous cancer.